2013
DOI: 10.1007/s11256-013-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Being Black, Male, and Gifted in Miami: Prevalence and Predictors of Placement in Elementary School Gifted Education Programs

Abstract: Although it is well established that Black male students are underrepresented in gifted educational programs in the United States, due to a scarcity of longitudinal prospective research, little is known about the protective factors at the child, family, and school level that increase the probability of Black male students being identified as gifted during early elementary school. Using data from the Miami School Readiness Project, we followed 6,926 low-income Black males from preschool through 5th grade to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
2
17
0
1
Order By: Relevance
“…Rather, other factors such as how giftedness is narrowly interpreted, teacher bias, and the procedures and instruments used for gifted identification contribute to under representation in gifted education (Ford, 2010;Ford and Moore, 2013;Ford and Whiting, 2010;Harradine et al, 2013;McBee, 2006). Research also finds positive educational outcomes when African-American and Latina/o students are afforded the opportunity to participate in gifted education and advanced curricula (Card and Giuliano, 2014;Mattern et al, 2009;Rose, 2013;Winsler et al, 2013). However, these students often have negative school experiences replete with disproportionate suspension rates beginning in preschool (US DOE OCR, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, other factors such as how giftedness is narrowly interpreted, teacher bias, and the procedures and instruments used for gifted identification contribute to under representation in gifted education (Ford, 2010;Ford and Moore, 2013;Ford and Whiting, 2010;Harradine et al, 2013;McBee, 2006). Research also finds positive educational outcomes when African-American and Latina/o students are afforded the opportunity to participate in gifted education and advanced curricula (Card and Giuliano, 2014;Mattern et al, 2009;Rose, 2013;Winsler et al, 2013). However, these students often have negative school experiences replete with disproportionate suspension rates beginning in preschool (US DOE OCR, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, many African-American gifted males experience success and demonstrate resilience in the face of hindrances. Winsler et al (2013) found that African-American boys who started kindergarten with greater cognitive, language, fine motor and behavioral readiness skills were more likely to be identified for gifted programming. Thus, attending public school prekindergarten programs increased the chances of being identified as gifted compared to attendance at community-based preschool programs.…”
Section: Gifted African-american Malesmentioning
confidence: 97%
“…Some individuals suffer from ethnicityrelated backlash when their attempts to achieve individuation are perceived by members of their own ethnic group as deviant behavior. Theories related to this phenomenon indicate that engaging in this form of backlash is a means of maintaining certain stereotypes and eliciting own-group conformity pressure upon the target (Contrada et al, 2001;Nicholls & Stukas, 2011;Winsler et al, 2013). Previous research suggests that selfmonitoring is important for resilience against the backlash effect (Bachman, O'Malley, Freedman-Doan, Trzesniewski, & Donnellan, 2011;O'Neill & O'Reilly, 2011), thereby indicating that high and low self-monitors may perceive this form of stress differently.…”
Section: Self-monitoringmentioning
confidence: 99%
“…A review of the literature shows that ethnicityrelated backlash often contributes to sociability problems, emotional issues such as decreased achievement gaps among different ethnic groups in many schools, but especially high schools and colleges (Fryer & Torelli, 2010;Hasana & Bagdeb, 2013;Winsler et al, 2013). The research also indicates that self-monitoring can be used to effectively thwart backlash in workplace settings (Brescoll, 2012;O'Neill & O'Reilly, 2011), and the application of this technique in school settings may help students with similar experiences reduce or thwart backlash.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation